Вплив факторів на піноутворення в технології молочних десертів з використанням карагінану - Сабадош, Ганна Олександрівна (НТУ "ХПІ", 2010)
Сформульовано інноваційний задум піноподібної десертної продукції та розроблено модель інноваційної стратегії технології десертів молочних із використанням карагінанів, піноподібної структури, у межах якої встановлено механізм регулювання технологічних властивостей рецептурних компонентів, що закріплені як параметри технологічного процесу. Обґрунтовано використання йота-карагінану для виробництва піноподібної десертної продукції на основі молока.

Formulated innovative idea spumy dessert products and the developed model of the innovation strategy of technology of milk desserts using carrageenan, spumy structure within which is mounted the mechanism of regulation of the technological properties of recipe components, are set as parameters of technological process. It justifies the use of iota- carrageenan for the production spumy dessert products based on milk. Brought the feasibility of the use of the composition of whipped dairy desserts iota-carrageenan and starch which provide maximum foaming ability.The first task for development of a new range there is a scientific study technological processes, which could form the basis for practical implementation of new technologies and can fully be implemented in the enterprises of restaurant economy or the cooperation of restaurants with the milk-processing entities.
The influence of factors on the foaming technology of milk desserts using carrageenan
Keywords: йота-карагінан; піноутворююча здатність; купажування; адсорбційний шар; поверхневий натяг; spumy dairy desserts; iota-carageenan; blending; adsorption layer; surface tension